Pengaruh Posisi Pengelasan dan Gerak Eletroda Terhadap Kekuatan Sambungan Las Baja SS400: Pengaruh Posisi Pengelasan dan Gerak Eletroda Terhadap Kekuatan Sambungan Las Baja SS400 - Kusnadi, Khoirur rojikin; Nani Mulyaningsih; Fuad Hilmy (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2024)
SS400 steel can be used to make car bodies. Welding is needed to connect car body parts. Welding is a method of joining metals. The most common type of welding is SMAW welding, where the electrode functions as a filler metal during the joining process. In the welding system there are several electrode positions and movements, the focus point of this research is the strength of 400 steel welded joints which involve various horizontal and vertical welding positions as well as straight and C-type electrode movements during welding. The results of the research show that specimens in vertical welding position and electrode movement C have the highest joint strength value of 282.5 MPa, while specimens in horizontal welding position and straight electrode movement have the lowest value of 184.9 MPa. The criterion value for car body strength is in the range of 190–290 Mpa. Judging from the research data, the strength value is met.